Sistem Informasi Jasa Cuci Interior Rumah dan Mobil Menggunakan Metode User Acceptance Test - Muhammad Arif Bastari; Darmansah Darmansah; Diovianto Putra Rakhmadani (STMIK Budi Darma, 2022)
At this time, the development of science and technological progress is increasing and sophisticated, especially the use of computers and mobile phones that almost use them and have a significant impact. The usefulness of information technology becomes a management of information that is easier to use. The same is felt by the owner of Wowo Clean Solution, wanting to feel an easier dissemination of information but still experiencing a shortage of information and ordering systems that have not been computerized, resulting in the people of Purwokerto not knowing much about home and car interior cleaning services, thereby reducing orders for cleaning the interior of the house and car. Therefore, researchers build a system using the Waterfall Method or the waterfall method is a model developed for software development. The Waterfall method was chosen because this method can help the author to develop the first stage software system that will be built according to the needs of the user (user). This researcher builds a website using the PHP and MYSQL programming languages. The final result of this research is to analyze the response of using the wowo clean solution website. The response to the use of the webiste from the community uses the User Acceptance Test (UAT) model testing. UAT aims to determine the functionality of software testing. The final result of this research is to produce an information system, namely the wowo clean solution website and the results of the examiner's assessment using the user acceptance test with an average score of 80% so that it gets good criteria.